-2(5w-7)+9=-7

Simple and best practice solution for -2(5w-7)+9=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5w-7)+9=-7 equation:


Simplifying
-2(5w + -7) + 9 = -7

Reorder the terms:
-2(-7 + 5w) + 9 = -7
(-7 * -2 + 5w * -2) + 9 = -7
(14 + -10w) + 9 = -7

Reorder the terms:
14 + 9 + -10w = -7

Combine like terms: 14 + 9 = 23
23 + -10w = -7

Solving
23 + -10w = -7

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -10w = -7 + -23

Combine like terms: 23 + -23 = 0
0 + -10w = -7 + -23
-10w = -7 + -23

Combine like terms: -7 + -23 = -30
-10w = -30

Divide each side by '-10'.
w = 3

Simplifying
w = 3

See similar equations:

| 2x^3=40x | | y=10(-1)-3 | | n/24=30/100 | | G(p+2)=2x^2+2x+1 | | 8x-13=7x+2 | | 25=3(x+3)-x | | 2x-7y=-3 | | y=-3/2x-7 | | 5(2x-1)4x+17=5x+6(x+2) | | -(6+y-z)= | | -3-9+x=-89 | | (3x-6)/((x^2)-9) | | 5x^2-71x-282=0 | | 9x+8x-6x=41+3 | | 0.9x=0.7+0.8x | | -4y=-3x+8 | | 5x+2(5-15)=60 | | 4m+24=12m | | 112=8(6-3m)-8 | | y=10(-5)-3 | | 15+(-5)+(-2)= | | 1/3h-42/3-3=2/3h-6 | | 4(x^2+20x-12)=0 | | 4/14m=1/14 | | 3x^2+3x-18=-4 | | -9x-17=-11x+33 | | 136(-58x)=-70 | | |2q+3|=11 | | 3n-22=-60 | | 26x+18=5(5x+8) | | 3(x-5)+2=5-(x+2) | | (-4-5i)(2+10i)= |

Equations solver categories